Designing the Help Feature for Supporting Exploratory Search - QIU Minghui, QIU Yuqi (Nongye tushu qingbao xuebao, 2021)
[Purpose/Significance] The process of the user using the information search systems to complete the exploratory search task is also the process of constantly calling for the help feature. This paper aims to find the close relationship between the exploratory search and the help feature. [Method/Process] Based on the information search behavior model supporting exploratory search, this paper applies the literature review method to collect and analyze the research findings of the help feature of the information search systems. [Results/Conclusions] A knowledge system will be summarized about the general help feature of the information search systems and about the help feature of the information search systems for supporting exploratory search that supports surveying, chaining, filtering, browsing and differentiating, and some relative design principles will also be put forward.